2010
DOI: 10.3892/ijmm_00000423
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits melanogenesis through activation of the ERK signaling pathway

Abstract: Abstract. Baicalein is one of the major flavonoids in Scutellaria baicalensis. However, the effects of baicalein on melanogenesis are unknown. The objective of this study was to evaluate the depigmenting capacity of baicalein and to elucidate its mechanism of action. B16F10 mouse melanoma cells were used to examine the effect of baicalein on melanogenesis by measurement of melanin content and tyrosinase activity after treatment. To ascertain the baicalein activity, the effect on two protein kinases, ERK and Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…One of the extensively investigated transduction mechanisms involved in the melanogenesis process is the MAPKs pathway [42,46]. Previous studies have revealed that phosphorylation of p38 MAPK can induce through activate MITF expression, and also phosphorylation of JNK and ERK can reduce melanogenesis through MITF phosphorylation and its subsequent degradation on B16F10 cells [47][48][49][50][51]. We therefore examined the influence of the purified peptide treatment on the activation of JNK, ERK and p38 MAPK attempting to further understand the molecular mechanisms involved in the pigmentation property of the purified peptide by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…One of the extensively investigated transduction mechanisms involved in the melanogenesis process is the MAPKs pathway [42,46]. Previous studies have revealed that phosphorylation of p38 MAPK can induce through activate MITF expression, and also phosphorylation of JNK and ERK can reduce melanogenesis through MITF phosphorylation and its subsequent degradation on B16F10 cells [47][48][49][50][51]. We therefore examined the influence of the purified peptide treatment on the activation of JNK, ERK and p38 MAPK attempting to further understand the molecular mechanisms involved in the pigmentation property of the purified peptide by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many natural and synthetic agents have been found to inhibit melanogenesis in B16F10 cells through activation of the ERK and/or the Akt pathways. For example, baicalein, cimicifuga heracleifolia, and KHG22394 (a synthesized chemical) were found to decrease melanin synthesis by activating ERK or Akt [18,26,27] . Therefore, we are interested in the effects of [6]-shogaol on ERK and Akt activities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the MAPK kinase (MEK)/extracellular signal-regulated kinase (ERK) and the PI3K/Akt pathways have been shown to negatively regulate melanin synthesis in melanocytes and melanoma cells [14][15][16][17][18] . Currently, cosmetic products possessing whitening effects occupy a large proportion of the cosmetic market and have become more popular than ever in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also reported that baicalein inhibited melanogensis in B16F10 mouse melanoma cells by activating the ERK signaling pathway. Furthermore, in vitro studies revealed that the reduction of tyrosinase activity, downregulation of microphthalmia-associated transcription factor (MITF) protein expression, and activation of ERK have been involved in the mechanisms of baicalein-mediated inhibition of melanogensis [55]. Another study showed that baicalein inhibited the proliferation of B16F10 melanoma cells through catalyzing the formation of reactive oxygen species (ROS) by 12-lipoxygenase [56].…”
Section: Baicalein and Melanoma/skin Cancermentioning
confidence: 99%